Linear perspective as aesthetic form - Gornykh, Andrei (Ukrainian Cultural Studies, 2024)
Background. The article provides a theoretical reconstruction of the linear perspective functioning as more than just an artistic technique that emerged and became an attribute of paintings starting with the Italian Trecento, in particular, in the works of Giotto. The purpose of the article is to reveal the heuristic potential of aesthetic form not in reflecting the consequences of the economic landscape transformation, but in anticipating its transformation and directing the efforts of the subject in its reorganization. The research's methodology is focused on the dynamics of cultural forms through the optics of art history and aesthetic theory, as well as on socio-historical reconstruction of the context without trying to prevent vulgar sociological reductionism and economic determinism. This approach reveals the relationship between the aesthetic text and the context, and the former's potential in clarifying the subtext by articulating the serial principle's aesthetic value and promoting the modern historical type of cultural production and consumption. Methods. This artistic guideline transformed not only the order of the signifiers of the painting (in particular, it replaced the golden background, which had been mostly filled with geometric shapes, humanized the illusory space, and saturated it with mathematically verified figures and objects) but also the order of signifies in the logic of the "picture of the world" (rehabilitation of sensory perception, declaration of the infallibility eye, autonomization of vision, dominance of pictorial space, compression of time to the moment of now, unification of the status of a separate thing in the general order, legitimization of holistic anti-metaphysical programs). Results. The article reveals the connection between the antimetaphysical program of linear perspective in the artistic dimension and the Cartesian homology of space in the theoretical dimension. It also emphasizes the architectonic principle of linear perspective: the rhythmicity of geometric shapes, a stable balance of nodal points, and dynamics of basic forms' reproductions and repetitions. Conclusions. Conducted research substantiates the understanding of linear perspective not as a method of legitimizing the correct vision of things, but as a representation of the valid order and scale of the world through a clear coordinate system, aimed at unification of the system of things and equivalent exchange within it.
Keywords: linear perspective; historical form; cultural landscape; principle of seriality; anti-metaphysical program; aesthetic theory